2018
DOI: 10.1002/2017gb005751
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale Effects on Carbon Export: A Global Perspective

Abstract: Carbon export from the surface to the deep ocean is a primary control on global carbon budgets and is mediated by plankton that are sensitive to physical forcing. Earth system models generally do not resolve ocean mesoscale circulation ( scriptO(10–100) km), scales that strongly affect transport of nutrients and plankton. The role of mesoscale circulation in modulating export is evaluated by comparing global ocean simulations conducted at 1° and 0.1° horizontal resolution. Mesoscale resolution produces a small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(97 citation statements)
references
References 124 publications
1
85
0
Order By: Relevance
“…Therefore, the model configuration is called "mesoscale resolving" (Hallberg, 2013). The configuration of the ocean model is similar to recent high-resolution ocean/sea ice configurations of CESM in most other ways as well (e.g., Bryan and Bachman, 2015;Delman et al, 2018;DuVivier et al, 2018;Harrison et al, 2018;Johnson et al, 2016;Soares et al, 2019). For example, as in these previous versions, runoff is mapped to a broad swath of grid cells near the coast, there are no explicit overflow, tidal mixing, near-inertial mixing, submesoscale, or mesoscale parameterizations, time stepping is achieved using the time-averaged leap frog scheme with a time step of 3.6 min, subgrid-scale turbulent vertical transport of tracers and momentum is computed with the K-profile parameterization (KPP) of Large et al (1994), and subgrid-scale lateral transport is parameterized via a spatially variable biharmonic viscosity and diffusivity that scale with grid size as in Bryan and Bachman (2015).…”
Section: Model Setup 211 3-d Ocean/sea Ice Modelmentioning
confidence: 90%
See 2 more Smart Citations
“…Therefore, the model configuration is called "mesoscale resolving" (Hallberg, 2013). The configuration of the ocean model is similar to recent high-resolution ocean/sea ice configurations of CESM in most other ways as well (e.g., Bryan and Bachman, 2015;Delman et al, 2018;DuVivier et al, 2018;Harrison et al, 2018;Johnson et al, 2016;Soares et al, 2019). For example, as in these previous versions, runoff is mapped to a broad swath of grid cells near the coast, there are no explicit overflow, tidal mixing, near-inertial mixing, submesoscale, or mesoscale parameterizations, time stepping is achieved using the time-averaged leap frog scheme with a time step of 3.6 min, subgrid-scale turbulent vertical transport of tracers and momentum is computed with the K-profile parameterization (KPP) of Large et al (1994), and subgrid-scale lateral transport is parameterized via a spatially variable biharmonic viscosity and diffusivity that scale with grid size as in Bryan and Bachman (2015).…”
Section: Model Setup 211 3-d Ocean/sea Ice Modelmentioning
confidence: 90%
“…Here, we quantify the sensitivity of the climatological annual mean, seasonal cycle, and subseasonal variance of the MLD to subseasonal winds, via their effects on ocean surface stress and buoyancy flux, at the finest resolved spatial scales (3–11 km) in a global mesoscale‐resolving ocean/sea ice numerical circulation model for the first time. Although it is well known that subseasonal winds have a significant impact on the stress, buoyancy flux, and MLD, no previous study has quantified these impacts in a global model that resolves mesoscales, which generally dominate upper‐ocean variance (Delworth et al, ; Ferrari and Wunsch, ; Kirtman et al, ; Small et al, ; Wunsch, ) and have a significant impact on the mean and seasonal cycle of the MLD (DuVivier et al, ; Hausmann et al, ; Harrison et al, ; Lee et al, ; Sein et al, ). In this modeling context, the motivating questions for this study are as follows: What fraction of the climatological mean, seasonal cycle, and subseasonal variability of the MLD is attributable to subseasonal winds, and how do these fractions vary across the globe?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional view that the gravitational pump and mixed‐layer pump operate solely on large scales is also being reassessed. Studies have shown that upward vertical velocities associated with eddies and fronts can supply nutrients to the euphotic zone, locally promote biological production, and eventually modulate the sinking of POC (e.g., Harrison et al, ; Lévy et al, ; Mahadevan, ; McGillicuddy, ). This dynamically driven variability in the gravitational pump could be further reenforced by biological processes, such as zooplankton diel and seasonal vertical migrations, which are expected to locally add 10% to 200% to the passive sinking flux of POC (Jónasdóttir et al, ; Steinberg & Landry, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent observations have challenged this large-scale picture of the ocean by adding large fluctuations in ocean fluxes of carbon (Landschützer et al, 2015) and heat (e.g., Liu et al, 2016) at shorter timescales (season to decades). There are now robust evidences that eddies or mesoscale ocean structures also influence a number of biogeochemical processes across temporal and spatial scales (e.g., Bettencourt et al, 2015;Dufour et al, 2015;Gruber et al, 2011;Harrison et al, 2018;Lacour et al, 2017;Lévy & Martin, 2013;Mazloff et al, 2018;Munday et al, 2014;Oschlies, 2002;Resplandy et al, 2009;Resplandy et al, 2013;Sweeney et al, 2003;Villar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%